2022
DOI: 10.21105/astro.2207.05202
|View full text |Cite
|
Sign up to set email alerts
|

The Cosmic Graph: Optimal Information Extraction from Large-Scale Structure using Catalogues

Abstract: We present an implicit likelihood approach to quantifying cosmological information over discrete catalogue data, assembled as graphs. To do so, we explore cosmological parameter constraints using mock dark matter halo catalogues. We employ Information Maximising Neural Networks (IMNNs) to quantify Fisher information extraction as a function of graph representation. We a) demonstrate the high sensitivity of modular graph structure to the underlying cosmology in the noise-free limit, b) show that graph neural ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Furthermore, it has been shown that neural networks can also extract information, while marginalizing over baryonic effects, on 2D maps from state-of-the-art hydrodynamic simulations (Villaescusa-Navarro et al 2021a. These methods not only work for 2D/3D grids but can also be applied to galaxy and halo catalogs (Ntampaka et al 2020;Villanueva-Domingo & Villaescusa-Navarro 2022;Makinen et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it has been shown that neural networks can also extract information, while marginalizing over baryonic effects, on 2D maps from state-of-the-art hydrodynamic simulations (Villaescusa-Navarro et al 2021a. These methods not only work for 2D/3D grids but can also be applied to galaxy and halo catalogs (Ntampaka et al 2020;Villanueva-Domingo & Villaescusa-Navarro 2022;Makinen et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While GNNs have been previously used on halo catalogs from the Quijote simulations (Villaescusa-Navarro et al 2020) in Makinen et al (2022), there are several differences with that work. First, we concentrate on much smaller scales than Makinen et al (2022; 25 h −1 Mpc boxes versus 1000 h −1 Mpc).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using different summary statistics as input data, Perez et al (2022) are able to derive cosmological parameters without the need for additional input from theoretical models, thus providing a powerful generalization of the usual Monte Carlo-based methods. In particular, likelihood-free inference methods work by taking data directly from the simulations (without the need for summary statistics and, thus, model comparison), and many papers have shown competitive results compared with the usual statistical inference methods (Ravanbakhsh et al 2017;Hassan et al 2020;Mangena et al 2020;Ntampaka et al 2020;Villaescusa-Navarro et al 2021a;Shao et al 2022b;Cole et al 2022;Makinen et al 2022;. At a level closer to the observations and simulations, many papers exploring the halogalaxy connection are able to make predictions that are comparable to the output of numerical/analytical methods (Kamdar et al 2016;Jo & Kim 2019;Yip et al 2019;Zhang et al 2019;Kasmanoff et al 2020;Wadekar et al 2020;Moster et al 2021;Villanueva-Domingo et al 2021;Shao et al 2022a;Jespersen et al 2022;Delgado et al 2022;Lovell et al 2022;McGibbon & Khochfar 2022;von Marttens et al 2022;Rodrigues et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the context of cosmology, they do not impose any cut on the considered physical scales, and different physical symmetries (e.g., translational and rotational invariance) can be easily implemented in the models (see Villanueva-Domingo & Villaescusa-Navarro 2022). GNNs have been used for a variety of tasks, such as parameter inference (Shao et al 2022b;Anagnostidis et al 2022;Makinen et al 2022;, inferring halo masses (Villanueva-Domingo et al 2021), speeding up semi-analytic models (Jespersen et al 2022), and rediscovering Newton's law (Cranmer et al 2020).…”
Section: Introductionmentioning
confidence: 99%